Effects of Germinated Soybean on Protein Efficiency Ratio in Rats - Mesomya, Wanpen; Cuptapun, Yaovadee; Hengsawadi, Duangchan; Lohana, Saruda; Yaieiam, Sompoch (Pakistan Journal of Nutrition, 2015)
The objective of this study was to evaluate the effects of germinated soybean on protein efficiency ratio (PER) by feeding male Sprague-Dawley rats with 10% protein in 4 experimental diets containing casein (control), soy protein isolate (SPI), ungerminated soybean (UGS) and germinated soybean (GS). PER was weight gained of rats consumed experimental diet divided by protein intake. The diets were prepared from 4 formulas by AOAC, with the following composition: 10% test protein, 8% oil, 5% water, 5% AIN-mineral, 1% AIN-vitamin, 1% cellulose, 35% sucrose and 35% corn starch. The results showed that PER were not significantly different among the rats fed with UGS (2.18±0.22) and GS (2.18±0.16) diets. The findings indicated that 2 days germinated soybean produced the same effect as ungerminated soybean on PER and growth rate in rats.